Assessment of mesenchymal stem cells for the treatment of spinal cord injury: a systematic review and network meta-analysis - Wang, Runfang; Wang, Yiding; Yan, Fangning; Sun, Jinqing; Zhang, Tianyu (Frontiers in Cellular Neuroscience, 2025)
ObjectiveThis study aims to explore the clinical efficacy of mesenchymal stem cell (MSC) transplantation in the treatment of patients with spinal cord injury (SCI) through a network meta-analysis and to discuss the optimal transplantation strategy for treatment.MethodsWe conducted a computer search of clinical randomized controlled studies on MSC treatment for SCI in databases including PubMed, Web of Science, Cochrane Library, Embase, China National Knowledge Infrastructure (CNKI), Chinese Science and Technology Journal Database (VIP), Wanfang Database, and Chinese Biomedical Literature Service System (SinoMed) up to March 2024. Two researchers independently completed literature screening and data extraction according to the inclusion and exclusion criteria and used RevMan 5.4 software to assess the quality of the included studies. Network meta-analysis was performed using Stata 16.0 software.ResultsA total of 18 studies were included in the analysis. The results showed that MSCs significantly improved motor, sensory, and activities of daily living activities after SCI. Network meta-analysis indicated that umbilical cord mesenchymal stem cells (UCMSCs) were the most effective cell source, and intrathecal injection (IT) was the optimal transplantation method.ConclusionThe study suggests that the current use of UCMSCs for IT transplantation may be the best transplantation strategy for improving functional impairment after SCI. Further high-quality studies are still needed to validate the results of this study and to ensure the reliability of the results.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier [CRD42023466102].